The Influence of Marketing Strategies, Service Performance, and Trust on Public Attention in Merdeka Savings Goods at KSPPS BMT Istiqlal Pekalongan - Lestari, Putri; Hudaya, Fadli (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
BMT Istiqlal is one of the first Islamic financial institutions established in the city of Pekalongan in 1995. Its initial purpose was to assist micro and small businesses due to their limited capital and limited access to banking services at the time. This was achieved by providing loans, also known as financing, with repayments made in installments or at a specified time. Other goods offered include Simapan Savings, Sifitri, Saras, General Investment, Term Investment, SMESS, Tafaqur, Education, Tahajud, Askesos, Simpatiq, Umrah, Merdeka, Ziarah, Musyarakah Financing, Mudharabah Financing, Murabahah Financing, and Qordhul Hasan Financing. The current research aims to evaluate the influence of marketing strategies, service performance, and trust on public attention in Merdeka savings goods at KSPPS BMT Istiqlal Pekalongan. This is a quantitative study. The sample was determined using purposive sampling with the Slovin method. Data collection was conducted by distributing questionnaires via Google Forms to clients, and the findings were tested using SPSS. The tests conducted include: 1. Descriptive Analysis Test, 2. Classical Assumption Test consisting of Normality Test, Multicollinearity Test, Autocorrelation Test, Heteroscedasticity Test, 3. Hypothesis Test consisting of t-Test, F-Test, and Determination Coefficient Test. The findings of the current research indicate that Marketing Strategy, Service performance, and Trust have a significant positive effect on savings attention, with a t-value of 6.968 > t-table 1.9839 and a significance level of 0.000< α = 0.05. The Adjusted R-Square value is 0.506, meaning that 50.6% of the attention in saving can be explained by the independent variables in the research.